SIGNIFIKANSI PENINGKATAN KUALITAS KOMPETENSI PENGAJARAN BAHASA ARAB PADA ANAK USIA DINI - Abd Aziz (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Abstract: This paper discusses the factors that cause the low quality of Arabic language learning standards in early childhood. The analysis reveals some of the root causes that contribute to this problem. First, the excessive focus on numerical assessment and assessment in language learning reduces the overall quality of Arabic language education. Such an approach neglects the comprehensive development of early childhood Arabic language competence. Second, the lack of a structured or well-coordinated early childhood education curriculum leads to ambiguity in learning objectives and selection of relevant material. As a result, this hinders the effectiveness of early childhood Arabic learning and produces poor quality results. Third, the use of outdated early childhood teaching methods that are not in accordance with the current developments in learning Arabic hinders students' understanding and interest in learning. The lack of innovative teaching methods adapted to the needs of students has a detrimental effect on the quality of early childhood Arabic education. Finally, teachers' inadequate qualifications and competence in Arabic linguistics, both modern and classical, as well as aspects of language culture, significantly impair the quality of Arabic learning. The quality of teaching plays an important role in raising the standard of Arabic language education. In conclusion, addressing these factors is very important to improve the quality of Arabic learning standards. Keywords: Educational Curriculum; Teaching Methods; Teacher Qualifications and Competencies; Quality of Arabic Language Learning